2011
DOI: 10.1002/jcb.23000
|View full text |Cite
|
Sign up to set email alerts
|

Metformin sensitizes insulin signaling through AMPK‐mediated pten down‐regulation in preadipocyte 3T3‐L1 cells

Abstract: Insulin resistance is the primary cause responsible for type 2 diabetes. Phosphatase and tensin homolog (PTEN) plays a negative role in insulin signaling and its inhibition improves insulin sensitivity. Metformin is a widely used insulin-sensitizing drug; however, the mechanism by which metformin acts is poorly understood. To gain insight into the role of PTEN, we examined the effect of metformin on PTEN expression. Metformin suppressed the expression of PTEN in an AMP-activated protein kinase (AMPK)-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
23
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 39 publications
4
23
0
1
Order By: Relevance
“…We demonstrated that a reciprocal relationship exists between AMPK and PTEN in the L-carnitine-mediated activation of PPARα in carboplatin-treated RTCs. These findings are consistent with those of a previous study, which showed that metformin, an insulin-sensitizing drug, suppressed the expression of PTEN through an AMPK-dependent mechanism in preadipocyte 3T3-L1 cells [39]. By contrast, AMPK knockdown eliminated the effects of metformin on reducing PTEN, suggesting that AMPK is involved in the regulation of PTEN.…”
Section: Discussionsupporting
confidence: 93%
“…We demonstrated that a reciprocal relationship exists between AMPK and PTEN in the L-carnitine-mediated activation of PPARα in carboplatin-treated RTCs. These findings are consistent with those of a previous study, which showed that metformin, an insulin-sensitizing drug, suppressed the expression of PTEN through an AMPK-dependent mechanism in preadipocyte 3T3-L1 cells [39]. By contrast, AMPK knockdown eliminated the effects of metformin on reducing PTEN, suggesting that AMPK is involved in the regulation of PTEN.…”
Section: Discussionsupporting
confidence: 93%
“…Metformin has well-established actions as an insulin and leptin sensitizer, in addition to its more recent characterization as an incretin sensitizer in the ␤-cell (36,59,60). Therefore, we also investigated the effects of metformin as an L cell sensitizer in vitro, using the same timeframe (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…Our results show the involvement of PTEN on TNF-α-induced reduced vascular insulin responses. There is evidence showing that PTEN modulates hyperglycemia and insulin resistance [54]. In addition, PTEN deletion in pancreatic α-cells protects against HFD-induced insulin resistance [55].…”
Section: Discussionmentioning
confidence: 99%